Legal Analysis of Islamic Family Civil Dispute Settlement Through Mediation - Norcahyono Norcahyono (Leges Privatae, 2025)
The resolution of Islamic family civil disputes through mediation has been regulated in national regulations, particularly in Supreme Court Regulation (Perma) No. 1 of 2016. However, the implementation of this policy still faces various obstacles that hinder its effectiveness in peacefully resolving family disputes. This study aims to analyze the regulations governing mediation in the resolution of Islamic family disputes in Indonesia, evaluate the effectiveness of the applicable laws, and provide recommendations to enhance the role of mediation in the religious court system. Using a normative juridical method with a statute approach, this research examines how existing regulations have been implemented in practice and whether there is a need for revisions or improvements in the mediation system. The findings indicate that although mediation is mandatory in family dispute resolution, its success rate remains low due to limited public awareness, a shortage of certified mediators, and a lack of supervision and evaluation of its effectiveness.Therefore, strengthening the role of mediation is necessary by increasing mediator capacity, promoting the benefits of mediation to the public, and reinforcing regulations to ensure the optimal implementation of mediation. Thus, mediation is expected to become an effective solution in reducing the burden of cases in religious courts and achieving a more harmonious and fair resolution of family disputes.